Heterocellularity and Cellular Cross-Talk in the Cardiovascular System - Perbellini, Filippo; Watson, Samuel A.; Bardi, Ifigeneia; Terracciano, Cesare M. (Frontiers in Cardiovascular Medicine, 2018)
Cellular specialization and interactions with other cell types are the essence of complex multicellular life. The orchestrated function of different cell populations in the heart, in combination with a complex network of intercellular circuits of communication, is essential to maintain a healthy heart and its disruption gives rise to pathological conditions. Over the past few years, the development of new biological research tools has facilitated more accurate identification of the cardiac cell populations and their specific roles. This review aims to provide an overview on the significance and contributions of the various cellular components: cardiomyocytes, fibroblasts, endothelial cells, vascular smooth muscle cells, pericytes and inflammatory cells. It also aims to describe their role in cardiac development, physiology and pathology with a particular focus on the importance of heterocellularity and cellular interaction between these different cell types.